Covid-19 and the Indian Stock Market Behaviour : Do Government Initiatives Really Matter? - Dey, Sanjeeb Kumar; Sharma, Debabrata (Indian Journal of Research in Capital Markets, 2022)
The primary purpose of this study was to investigate the effect of the COVID-19 pandemic on the major Indian stock exchanges with specific regard to the government’s initiatives to control the same. The study covered a period of seven months, from February 2020 to August 2020, spanning three phases – infant, lockdown, and unlock phase – during the first wave of the COVID - 19 pandemic. The stock market indices at the closing time of the market were taken as the dependent variable, while the daily infection reported, the number of equity stocks traded, and the total turnover in the stock market were taken as independent variables. Using the data on daily reported COVID infections in India, the impact assessment was carried out with the help of a panel data regression analysis for the short-run and long-run in relation to the Government initiatives and control measures. During the infant phase, we found a strong negative relationship between daily reported COVID infections and stock market indices. Subsequently, even despite an increase in infections in the following phases, it was established that the stock markets responded positively due to the government’s proactive COVID -19 management initiatives.